Mongolia InfraSAP : Infrastructure for Connectivity and Economic Diversification - World Bank (World Bank, Ulaanbaatar, 2020)
Like many emerging economies, policy discussions on social and economic growth in Mongolia often gravitate to transport, energy and digital infrastructure as the backbone. ‘What infrastructure?’ and ‘infrastructure for what?’ are equally important questions given the aspirations to unlock new drivers of growth beyond mining and export of primary products. Mongolia’s vast territorial expanse and low population density create unique challenges for economic development in general and infrastructure investments in particular. Sandwiched between China and the Russia, two of the largest countries and economies in the world, Mongolia is the least densely populated country in the world. With just over 3.2 million people inhabiting a territory of 1.564 million square kilometers (more than six times the size of the United Kingdom and less than a third the population of London), Mongolia has a population density of 2.1 people per square kilometer. About half the population—some 1.4 million people—live in the capital city Ulaanbaatar. The rest of the population is spread across small urban centers and vast steppes. Given the spatial and density challenges, the conventional ‘build and they shall come’ approach to developing infrastructure has proved sub-optimal. Mongolia has some of the largest average transport distances (600km) and highest logistics costs (30% of GDP). The infrastructure challenge is made worse by the limited financing options. This infraSAP presents a more sophisticated approach which incorporates strategic value chain analysis and disaggregated modeling of freight movements, and then targets infrastructure investment for amplified impact. In this approach, infrastructure is located at the highest concentrations of economic activity and is developed as part of an integrated national logistics system. This surgical approach informs more targeted policy decisions on how to use scarce resources to accelerate economic diversification and competitiveness while addressing institutional bottlenecks.